Knowledge, attitude and practices of design for safety (DfS): A dynamic insight between academics and practitioners in Malaysia. (February 2022) - Che Ibrahim, Che Khairil Izam; Belayutham, Sheila; Manu, Patrick; Mahamadu, Abdul-Majeed; Cheung, Clara Man
Highlights: Knowledge, attitude and practices of design for safety (DfS) among academics and practitioners in Malaysia are investigated. There are similarities and differences of perceptions about DfS between the academics and practitioners. Culture, engagement and organizational lifelong are critical for DfS learning. Funding, early learning, capacity building and guidance influence DfS effectiveness. Abstract: Design for safety (DfS) is increasingly gaining relevance in improving construction occupational safety and health. Specifically, Occupational Safety and Health in Construction Industry (Management) (OSHCI(M)) guidelines were established in Malaysia to improve DfS practices. Therefore, the need to gauge the DfS knowledge, attitude and practices (KAP) of construction stakeholders is significant. The objective of this paper is twofold. Firstly, to investigate the DfS KAP between the academics and practitioners. Secondly, to recommend the mechanisms for improving the learning of DfS among the key stakeholders. This study used a KAP survey and a discussion forum from five DfS workshops, followed by the development of framework using a Causal Loop Diagram (CLD). The findings revealed that stakeholders are very positive towards DfS implementation. Creating a culture of shared DfS learning, continuous engagement in education and training, and organisational lifelong DfS learning were highlighted as ways to improve DfS learning. The CLD shows that the effectiveness of DfS learning is attributed to funding, early learning, capacity building, and practical DfS guidance. This study helps advance DfS learning towards improving the KAP of construction professionals, hence facilitating DfS diffusion within and beyond the organisation and construction projects.